Consciousness - Weisberg, Josh (Key concepts in philosophy., 2014)
Each of us, right now, is having a unique conscious experience. Nothing is more basic to our lives as thinking beings and nothing, it seems, is better known to us. But the ever-expanding reach of natural science suggests that everything in our world is ultimately physical.